Functional evolution of Lepidoptera olfactory receptors revealed by deorphanization of a moth repertoire - Arthur de Fouchier (Nature Portfolio, 2017)
The range of odours that an insect can detect depends on its olfactory receptors. Here, the authors functionally characterize the olfactory receptor repertoire of the mothSpodoptera littoralis using the Drosophilaempty neuron system and reconstruct the evolution of these receptors in the Lepidoptera.